Biodegradable nanocomposite coatings accelerate bone healing: In vivo evaluation - Mehdi Mehdikhani-Nahrkhalaji; Mohammad Hossein Fathi; Vajihesadat Mortazavi; Sayed Behrouz Mousavi; Ali Akhavan; Abbas Haghighat; Batool Hashemi-Beni; Sayed Mohammad Razavi; Fatemeh Mashhadiabbas (Wolters Kluwer Medknow Publications, 2015)
Background: The aim of this study was to evaluate the interaction of bioactive and biodegradable poly (lactide-co-glycolide)/bioactive glass/hydroxyapatite (PBGHA) and poly (lactide-co-glycolide)/bioactive glass (PBG) nanocomposite coatings with bone. Materials and Methods: Sol-gel derived 58S bioactive glass nanoparticles, 50/50 wt% poly (lactic acid)/poly (glycolic acid) and hydroxyapatite nanoparticles were used to prepare the coatings. The nanocomposite coatings were characterized by scanning electron microscopy, X-ray diffraction and atomic force microscopy. Mechanical stability of the prepared nanocomposite coatings was studied during intramedullary implantation of coated Kirschner wires (K-wires) into rabbit tibia. Titanium mini-screws coated with nanocomposite coatings and without coating were implanted intramedullary in rabbit tibia. Bone tissue interaction with the prepared nanocomposite coatings was evaluated 30 and 60 days after surgery. The non-parametric paired Friedman and Kruskal-Wallis tests were used to compare the samples. For all tests, the level of significance was P < 0.05. Results: The results showed that nanocomposite coatings remained stable on the K-wires with a minimum of 96% of the original coating mass. Tissue around the coated implants showed no adverse reactions to the coatings. Woven and trabecular bone formation were observed around the coated samples with a minimum inflammatory reaction. PBG nanocomposite coating induced more rapid bone healing than PBGHA nanocomposite coating and titanium without coating (P < 0.05). Conclusion: It was concluded that PBG nanocomposite coating provides an ideal surface for bone formation and it could be used as a candidate for coating dental and orthopedic implants.